The mediating role of psychological capital in the relationship between EFL learners’ L2 grit and L2 WTC - Chen, Xiaoming; Alruwaili, Areej Radhi; Azari Noughabi, Mostafa; Ghasemi, Ameneh; Zhen, Changhui (Frontiers in Psychology, 2025)
IntroductionThe key role of L2 grit has been acknowledged in English as a foreign language (EFL) learners’ linguistic and psychological development. However, there is still debate regarding the role of L2 grit in enhancing EFL learners’ willingness to communicate (WTC) in L2. Furthermore, due to the novelty of the concept of psychological capital (PsyCap) in the field of foreign language education, little is known about its mediating role in the relationship between L2 grit and WTC.MethodsThe current study used valid, online questionnaires and employed structural equation modelling (SEM) to test whether Chinese EFL learners’ (N = 664) PsyCap can mediate the relationship between their domain-specific grit and WTC.ResultsThe results indicated that Chinese EFL learners’ PsyCap partially mediated the relationship between L2 grit and WTC. Therefore, L2 grit impacted EFL learners’ WTC in L2 both directly and indirectly through their positive psychological resources such as optimism, resilience, efficacy, and hope.DiscussionThe findings highlight the criticality of positive psychological states in language classroom settings where EFL learners can enhance their tendency to communicate in L2 with higher levels of perseverance of effort and consistency of interest.